PENGARUH LAYANAN INFORMASI MENGGUNAKAN METODE NHT (NUMBERED HEADS TOGETHER) TERHADAP KREATIVITAS BELAJAR PESERTA DIDIK SMP MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2016/2017 - Mudaim, Mudaim; Ristiawati, Ristiawati (Lembaga Penelitian UM Metro, 2018)
method of NHT (numbered heads together) on the creativity of learners of class VIII B SMP Muhammadiyah 1 Metro year 2016/2017 year. The design of this research is One-Group Pretest-Posttest Design. In the data collection in this study using questionnaires. Data analysis used is t test. Judging from the difference of change of result of average result of pre-test post-test of creativity learn equal to 9,9. Testing the hypothesis obtained t calculation = 9,446 > ttabel = 2.045 of significant 0.05 and degrees of freedom (db = N -1 = 30 -1 = 29). The conclusion of this research is information service using NHT method (numbered heads together) influence to creativity learners SMP Muhammadiyah 1 Metro TP. 2016/2017.